RAA and υn: Relativistic transport approach for charm and bottom toward a more solid phenomenological determination of Ds(T) - Sambataro Maria Lucia; Plumari Salvatore; Minissale Vincenzo; Parisi Gabriele; Greco Vincenzo (EPJ Web of Conferences)
Quasi-Particle Model (QPM) allows for a good description of the main features of thermodynamics computed via lattice QCD (lQCD) and for charm quark supplies a satisfying description of RAA and υ2,3 of D mesons. Within an event-by-event full Boltzmann transport approach followed by a hybrid hadronization via coalescence plus fragmentation, we investigate the extension to bottom quark dynamics discussing predictions for RAA and υ2,3 of B mesons comparing to the available experimental data by ALICE collaboration on electrons from B meson decay. Furthermore, we extend our QPM approach to a more realistic model in which partonic propagators explicitly depend on quark momentum (QPMp) following Dyson-Schwinger studies. The QPMp improves the description of quark susceptibilities computed via lQCD, understimated in the standard QPM approach and entails a Ds with a stronger nonperturbative behaviour near to Tc which leads to a better agreement with the recent lQCD data.